1983
DOI: 10.1136/sti.59.3.176
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ceftriaxone with cefoxitin in the treatment of penicillin-resistant gonococcal urethritis.

Abstract: SUMMARY Since cefoxitin has been shown to be an effective alternative to spectinomycin for the treatment of infections due to penicillinase-producing strains of Neisseria gonorrhoeae (PPNG) its efficacy was compared with that of a new cephalosporin, ceftriaxone (R013-9904). One hundred and twenty eight men with culture-confirmed gonococcal urethritis were treated with either 250 mg of ceftriaxone intramuscularly or 2 g of cefoxitin intramuscularly with oral probenecid 1 g. The incidence of penicillin-resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1984
1984
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…Twenty-five studies used intramuscular injection monotherapy that involved 6422 patients and compared the efficacy of 12 different drugs . Nineteen of these studies reported adverse reactions in 569 patients and the safety of 11 drugs was assessed [28][29][30][31][32][33][34][35][37][38][39][40][41][42][45][46][47]50,51]. Similarly, 19 studies focused on oral monotherapy [52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71].…”
Section: Literature Search Process and Study Characteristicsmentioning
confidence: 99%
“…Twenty-five studies used intramuscular injection monotherapy that involved 6422 patients and compared the efficacy of 12 different drugs . Nineteen of these studies reported adverse reactions in 569 patients and the safety of 11 drugs was assessed [28][29][30][31][32][33][34][35][37][38][39][40][41][42][45][46][47]50,51]. Similarly, 19 studies focused on oral monotherapy [52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71].…”
Section: Literature Search Process and Study Characteristicsmentioning
confidence: 99%
“…Other parenteral cephalosporins have been studied and recommended as alternative regimens 8. These include ceftizoxime 500 mg IM,92-94 cefoxitin 2 gm IM with 1gm of probenecid,95-97 and cefotaxime 500mg IM 98-100. Cefuroxime 1.5gm IM is occasionally used in the United Kingdom.…”
Section: Cephalosporins For the Treatment Of Gonococcal Infectionsmentioning
confidence: 99%
“…Cefotetan, the subject of this study, was such a compound that has demonstrated clinical success against gonorrhea (7,11,20). These features are shared with cefoxitin, a similar cephamycin compound (2,12,17,21).…”
Section: U>40mentioning
confidence: 93%
“…Susceptibility tests for cefoxitin, another cephamycin, against gonococci have recently been standardized by using GC agar base medium (9). These more simplified procedures should predict the favorable clinicalbacteriologic response to single-dose gonorrhea therapy, e.g., 2 g of cefoxitin plus a predose of 1 g of probenicid (9,12,17,21). Since cefotetan has superior pharmacokinetics compared with those of cefoxitin, probenicid is not required (16).…”
mentioning
confidence: 99%